If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 85 + 17x = -87 + 13x Solving 85 + 17x = -87 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 85 + 17x + -13x = -87 + 13x + -13x Combine like terms: 17x + -13x = 4x 85 + 4x = -87 + 13x + -13x Combine like terms: 13x + -13x = 0 85 + 4x = -87 + 0 85 + 4x = -87 Add '-85' to each side of the equation. 85 + -85 + 4x = -87 + -85 Combine like terms: 85 + -85 = 0 0 + 4x = -87 + -85 4x = -87 + -85 Combine like terms: -87 + -85 = -172 4x = -172 Divide each side by '4'. x = -43 Simplifying x = -43
| 11x-6=6x+14 | | 5(x+2)=3k-1 | | x+x+2+x+4+x+6=464 | | -5.9-(-4.9)= | | x+x+1+x+2=156 | | 102=9x | | -136+2x=6x+132 | | y=20+3x | | 9=3v+37+4v | | y=0.15x+2.94 | | 10x-6=5x+9 | | 0.4m+4=7.6 | | 10-4x-pix=0 | | 2=-2+22 | | -3z+5=26 | | 3=-2y-1.6 | | 95-5x=65 | | 8=17-x | | y=4x+33 | | 156-22x=109-17x | | 27-x=27 | | 126+8m=254 | | x+x+2+x+4+x+6=344 | | f(3)=-3.3-2 | | -y=-9x+33 | | -8x-x=24x | | 3.64x+49=13.2496+7x | | -3=2p+1 | | 24n-98=238 | | (4xy^3)(3x^3y^5)= | | f(3)=-3(3)-2 | | Y-64=-3.50(x-0) |